2007
DOI: 10.1111/j.1745-4549.2007.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Functional Properties of Yam Beans (Sphenostylis Stenocarpa)

Abstract: The proximate and selected functional properties of five flours from yam bean (YB) made after the grains were not processed (raw) and processed as boiled, fermented, roasted and malted, were determined. The functional properties were water and fat absorption, gelation, emulsification and whippability. An improvement was observed for protein content of flours processed beans compared to raw flour. Fermentation improved the oil content of the flour. The emulsifying and foaming capacities (50.7 and 40.20%, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
22
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 23 publications
11
22
1
1
Order By: Relevance
“…These values are similar to those reported for other protein concentrates and isolates produced from legumes including some soy proteins (Fernandez-Quintela et al, 1997;L'Hocine, Boye, & Arcand, 2006;Lee, Htoon, Uthayakumaran, & Paterson, 2007;Obatolu, Fasoyiro, & Ogunsunmi, 2007;ParedesLopez et al, 1991;Wong & Kitts 2003). For each pulse, the protein extract produced using IEP had a higher water holding capacity than the one produced using UF (the only exception was the red lentil protein concentrate) (Fig.…”
Section: Water Holding Capacitysupporting
confidence: 89%
“…These values are similar to those reported for other protein concentrates and isolates produced from legumes including some soy proteins (Fernandez-Quintela et al, 1997;L'Hocine, Boye, & Arcand, 2006;Lee, Htoon, Uthayakumaran, & Paterson, 2007;Obatolu, Fasoyiro, & Ogunsunmi, 2007;ParedesLopez et al, 1991;Wong & Kitts 2003). For each pulse, the protein extract produced using IEP had a higher water holding capacity than the one produced using UF (the only exception was the red lentil protein concentrate) (Fig.…”
Section: Water Holding Capacitysupporting
confidence: 89%
“…Heating has been reported to decrease the protein solubility, emulsification and foaming capacity of low-fat soya flour (Heywood, Myers, Bailey, & Johnson, 2002). Similar results were reported by Yu, Ahmedna, and Goktepe (2007) for peanut flour and by Obatolu, Fasoyiro, and Ogunsunmi (2007) for yam bean flour.…”
Section: Introductionsupporting
confidence: 89%
“…Foaming properties (FC or FE) are related to protein content, protein structure and processing treatments (Paredes-Lopez et al, 1991;Obatolu, et al, 2007). Obatolu et al, (2007), reported greater foaming capacities in raw yam bean in comparison with boiled yam bean, which suggested that a thermal processing treatment may lower the FC. The differences in foaming properties of the pulse ingredients could thus be due to differences in protein content as well as processing treatments which could in some instances result in protein denaturation.…”
Section: Functional Properties Of Pulse Ingredientsmentioning
confidence: 99%
“…Interestingly, the solubility of both the chickpea flour and lentil flour (at the region of highest solubility) was higher (60 -80%) than for pea protein concentrate (20-25%). Processing treatments used for the production of pulse ingredients can affect their functionality (Obatolu, Fasoyiro, & Ogunsunmi, 2007). In particular, production methods such as precooking and drum-drying or spray-drying can reduce the nitrogen solubility of pulse flours and ingredients (Carcea-Bencini, 1986).…”
Section: Functional Properties Of Pulse Ingredientsmentioning
confidence: 99%
See 1 more Smart Citation